Avian Influenza A(H5N1) Isolated from Dairy Farm Worker, Michigan, USA - Nicole Brock; Joanna A. Pulit-Penaloza; Jessica A. Belser; Claudia Pappas; Xiangjie Sun; Troy J. Kieran; Hui Zeng; Juan A. De La Cruz; Yasuko Hatta; Han Di; C. Todd Davis; Terrence M. Tumpey; et al. (Emerging Infectious Diseases)
Influenza A(H5N1) viruses have been detected in US dairy cow herds since 2024. We assessed the pathogenesis, transmission, and airborne release of A/Michigan/90/2024, an H5N1 isolate from a dairy farm worker in Michigan, in the ferret model. Results show this virus caused airborne transmission with moderate pathogenicity, including limited extrapulmonary spread, without lethality.